2017
DOI: 10.1007/s10517-017-3737-7
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroquercetin Improves Microvascularization and Microcirculation in the Brain Cortex of SHR Rats during the Development of Arterial Hypertension

Abstract: The effects of dihydroquercetin (50 mg/kg intragastrically daily for 6 weeks) on the density of capillary network (mean number of capillaries per mm), mean capillary diameter, structure of capillary network, capillary diameter distribution (<3, 3-5, 5-7, and 7-9 μ), and local cerebral blood flow (by laser Doppler) in the visual cortex were studied in SHR rats during the development of arterial hypertension (from the 6th to the 12th week of life). Normally, the systolic and diastolic BP progressively increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…Taxifolin is known to be an anti-oxidative agent [4], and beneficial effects of taxifolin have been reported. Previous reports showed possible beneficial effects of taxifolin using animal models, including improvement of microcirculation [5], hepatoprotective effects [6], anti-viral activity [7], and prevention of diabetic nephropathy [8] as well as cardiomyopathy [9]. Further, in vitro studies demonstrated that taxifolin exhibits anti-bacterial [10], anti-fungal [11], and anti-parasitic [12] effects, and taxifolin inhibits acetylcholinesterase and carbonic anhydrase isoenzymes [13].…”
Section: Introductionmentioning
confidence: 98%
“…Taxifolin is known to be an anti-oxidative agent [4], and beneficial effects of taxifolin have been reported. Previous reports showed possible beneficial effects of taxifolin using animal models, including improvement of microcirculation [5], hepatoprotective effects [6], anti-viral activity [7], and prevention of diabetic nephropathy [8] as well as cardiomyopathy [9]. Further, in vitro studies demonstrated that taxifolin exhibits anti-bacterial [10], anti-fungal [11], and anti-parasitic [12] effects, and taxifolin inhibits acetylcholinesterase and carbonic anhydrase isoenzymes [13].…”
Section: Introductionmentioning
confidence: 98%
“…The same genus of larches, the Dahurian larch (Larix gmelinii), and the Siberian or Russian larch (Larix sibirica) contain abundant taxifolin (dihydroquercetin) in the xylems [1,2]. Taxifolin is known to be an antioxidant agent [3], and is known for the many beneficial effects of taxifolin, such as improvement of microcirculation [4], hepatoprotective effects [5], anti-viral activity [6], and prevention of diabetic nephropathy [7] as well as diabetic cardiomyopathy [8]. In vitro studies have demonstrated that taxifolin exhibits anti-bacterial [9], anti-fungal [10], and anti-parasitic [11] effects, and also inhibitory activities against acetylcholinesterase and carbonic anhydrase isoenzymes [12].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a 2-week-long treatment of SHRs with TX (300 µg/kg) failed to reduce BP and ACE activity in the aorta, while the same dose of TX reduced ACE activity in WKY rats [186]. In contrast to EC, TX did not affect the age-dependent development of hypertension in SHRs, but it improved microcirculation of the brain tissue when administered at a dose of 50 mg/kg/day for 6 weeks intragastrically [71].…”
Section: Ec and Tx Action In Spontaneously Hypertensive And Borderline Hypertensive Ratsmentioning
confidence: 88%